Financial stability index, credit and external shocks in Malaysia - Koong, Seow Shin (2014)
This study examines the role of credit, internal and external shocks on financial stability in Malaysia spanning from April 1997 to December 2011, where the sample period consists of two major financial crises that affected Malaysian economy, namely the 1997/98 Asian Financial Crisis and 2008/09 Global Financial Crisis. Specifically, this study examines three specific objectives: (1) to develop Malaysian financial stability index and relate its predictive power on Malaysian business cycle, (2) to determine the detrimental or beneficial effect of credit on the Malaysian financial stability and (3) to investigate the effects of credit shocks and monetary policy shocks on the Malaysian financial stability. The first objective is motivated by the incapability of conventional macroeconomics indicators in predicting the likelihood of economic recession nowadays. More importantly, based on past studies, less attention is paid on the financial stability index in developing countries, except Osorio et al. (2011) and Tng et al. (2012). However, the financial stability index is developed to be a better measure with greater coverage of the Malaysian financial system compared to the existing financial conditions indexes. In addition, the forecasting tests used on the existing FCI developed by Osorio et al. (2011) are merely descriptive. Hence, its predictability of the FCI is unconvincing. In this part of study, a financial stability index is constructed using the dynamic factor model and a wide array of variables to measure the conditions of the Malaysian financial system. The empirical results demonstrate that the inclusion of the constructed financial stability index in the autoregressive model reduces the forecast errors. Further, the forecasted business cycle using the constructed index appears to be rational, properly scaled and provides incremental information in the short period of 3-month’s time. The empirical findings reveal that the constructed financial stability index is able to predict the Malaysian business cycle. The second objective is motivated by the increasing level of credit in Malaysia, especially the growth of household credit outpaces business credit. Further, a body of existing literatures found that rapid credit expansion is the main culprit of the likelihood of financial crisis. As a result, credit expansion is detrimental to the stability of financial system. By employing a non-parametric, OLS and GMM methods, the degree of synchronization between credit and financial stability is investigated. The empirical results suggest that an increasing level of credit would tighten the conditions of the financial system and ultimately cause financial instability, especially business credits. However, there is insufficient evidences to prove that household credit is detrimental to Malaysian financial stability. In sum, the growth-enhancing effect of credit and financial stability do not complement each other in Malaysia, especially when business credit expands. Lastly, the third objective is motivated by the openness of Malaysia, where Malaysia is a small open economy and the likelihood of the financial crisis could be transmitted from Malaysia's major trading partners due to its trade and financial linkages. Hence, using the structural VAR model, the effects of external shocks, such as a U.S. monetary policy shock, as well as internal shocks on Malaysian financial stability is examined. The impulse response results indicate that the Malaysian financial stability responds contemporaneously and significantly towards a U.S. monetary policy shock and domestic monetary policy shock; whereas it does not respond to either foreign credit or domestic credit shocks. However, the impact on the financial stability, after the shock, diminishes within a year. This study concludes that a U.S. monetary policy shock has indirect influenced on the macroeconomic fluctuations in Malaysia through affecting Malaysian financial stability.